Using Think Pair Share for Teaching Writing in Junior High School - Ayu Upadani Sukarta, Ni Kadek; Ari Wiryadi Joni, Dewa Ayu; Yudhi Pramawati, Anak Agung Istri (Journal on Studies in English Language Teaching (JOSELT), 2024)
There are four major English skills that Indonesian students must learn: namely listening, speaking, reading, and writing. Writing is one of the language skills needed to achieve language mastery. On the other hand, writing is an active process of conveying ideas using symbols and arranging them into a readable form. In addition, writing encourages the development of critical thinking skills. The main aim of this research is to apply Think Pair Share in teaching writing. The subjects in this research were class VIII students at SMPN 5 Mengwi. The class consisted of 32 students who were poor in writing, especially in writing paragraphs. Researchers used three tests to collect data: pre-test, post-test, and questionnaire. Researchers used the average score formula when calculating all of the subject's pre-test and post-test data. The results of the questionnaire in this research were used to determine and analyze the percentage of student responses to the techniques applied.